Evaluation of C-reactive protein (CRP) plasma concentration among women during labour and in early puerperium - Joanna Lebdowicz; Aleksandra Rajewska; Dorota Torbé; Andrzej Torbé (Kazimierz Wielki University, 2018)
Objectives: Calculation and analysis of CRP plasma concentration among women during labour and in the second day of puerperium in various clinical situations Material and methods: 317 participants about estimated due date (EDD) were included to the study and then divided into four groups: 1. Women with labour onset after previous rupture of membranes and spontaneous vaginal delivery - PROM (n= 97) 2. Women with labour onset at intact membranes and spontaneous vaginal delivery - non -PROM (n= 133) 3. Women who delivered by caesarean section for elective indications - ELCS (n= 58) 4. Women who delivered by caesarean section for emergency indications - EMCS (n= 29) Venous blood sampling for CRP plasma concentration evaluation was done in the course of labour or strictly before elective caesarean section and then, subsequently, on the second day of puerperium. Results: In all groups postdelivery CRP plasma level was significantly higher than in the course of labour (p < 0,001). CRP plasma concentration during labour among women who finally delivered vaginally was significantly higher in case of amniotic fluid leakage before the onset of labour, in comparison with this found in women with intact membranes (PROM = 6,30 mg/L vs non-PROM = 2,50 mg/L, p < 0,05). There was a significant difference between groups who gave birth by caesarean section. CRP level was lower among women who had elective caesarean section (EMCS 6,30 mg/L vs ELCS 4,15 mg/L, p < 0,05). In our study we found significantly higher puerperal CRP plasma level among women after caesarean section, as well for emergency as for elective indications, than among women after vaginal delivery, independently from ruptured or intact foetal membranes (p < 0.001). There was no difference in the CRP concentration on the 2nd of puerperium between two groups of women who gave birth vaginally, with or without membranes rupture before labour onset (PROM vs non-PROM, NS), same as between those who had caesarean delivery (ELCS vs EMCS, NS). Conclusions: 1. The increase of CRP plasma concentration follows the parturition and it is significantly higher after caesarean than after vaginal delivery 2. Intrapartum CRP level is higher among women with amniotic fluid leakage before the onset of labour, than in those with intact foetal membranes, what can suggest the participation of inflammatory response in the labour beginning with membranes rupture 3. CRP concentration on the second day of puerperium is similar in women after elective and emergency caesarean section 4. The assessment of CRP concentration as the only test in early puerperium is not useful for the decision making about antibiotic therapy 5. Because of early discharge of women from the hospital, as well after vaginal as caesarean delivery, the usefulness of CRP concentration assessment in early puerperium decreases progressively